The 5Cs of Positive Youth Development, Purpose in Life, Hope, and Well-Being Among Emerging Adults in Malaysia - Abdul Kadir, Nor Ba’yah; Mohd, Rusyda Helma (Frontiers in Psychology, 2021)
A substantial body of evidence supports Lerner and colleagues’ 5Cs model of positive youth development (PYD) in the United States (U.S.). Nonetheless, it remains unclear whether the 5Cs can be used to identify positive development in the under-researched Asian contexts, such as Malaysia. Thus, this study examined the 5Cs of PYD (competence, confidence, character, connection, and caring) and their importance to purpose in life, hope, and well-being in a sample of emerging adult undergraduate university students in Malaysia. Data were collected from 400 participants from 15 Malaysian universities (132 males, 268 females; ages ranged from 18 to 26 years old, M = 22). A hierarchical multiple regression analysis indicated that two of the 5Cs of PYD (confidence and connection) as well as hope were important to explaining variation in well-being. The findings imply that there are strong links between PYD, especially confidence and connection, and well-being, while purpose in life and hope were indirectly related to the 2Cs (confidence and connection) of PYD and well-being. Therefore, mental health professionals are encouraged to review and redefine their treatment design to include confidence, connection, purpose in life and hope when working with Malaysian emerging adult university students.